Patthollogiicall & Resiidues sttudy off Cadmiium Chlloriide iin rabbiitts - I., AL -Kaisie. B. (The Iraqi Journal of Veterinary Medicine, 2008)
IIn tthe prresentt rresearrch, tthe patthollogiicall effffectt off CdCll2 rresiidue sttudy wasdone on whiitte malle rrabbiitts.. 42 whiitte malle rrabbiitts werre rrandomlly diiviided iintto 2grroups :: 1stt grroup iinclluded 30rrabbiitts werre giiven CdCll2 13 Mg // kg // day fforr 12weeks viia drriinkiing watterr ..2nd grroup iinclluded 12rrabbiitts ffed on norrmall rrabbiitt diiett..The ffollllowiing parrametterrs werre obserrved on tthe above grroups::1– Clliiniicall siigns:: Trreatted rrabbiitts showed, vomiittiing and blloody diiarrrrhea ..2– Resiiduall iinvesttiigattiion on lliiverr and kiidney :: CdCll2 rresiidue prresentt morresiigniiffiicantt iin lliiverr and kiidney mosttlly att 8 and 12 weeks :: 108..0 , 447..0 mg//kgdrry weiightt iin lliiverr and 113..1, 447..0 mg//kg drry weiightt iin kiidney rrespecttiivelly ..3– Hiisttopatthollogiicall changes:: The lliiverr & kiidney off ttrreatted rrabbiitt showed iinlliiverr and kiidneys ttypiicall fforrm off macrrophage grranulloma surrrrounded by ffiibrrousconnecttiive ttiissue..